Biological inorganic chemistry : - Crichton, Robert R. (Elsevier, 2019)
Biological Inorganic Chemistry: A New Introduction to Molecular Structure and Function, Third Edition, provides a comprehensive discussion of the biochemical aspects of metals in living systems. The fascinating world of the role of metals in biology, medicine and the environment has progressed significantly since the very successful Second Edition of the book published in 2012. Beginning with an overview of metals and selected nonmetals in biology, the book supports the interdisciplinary nature of this vibrant area of research by providing an introduction to basic coordination chemistry for biologists and structural and molecular biology for chemists.